张爱玲的魂兮归来？夏志清的《中国现代小说史》与中国大陆文学史对张爱玲的接受限度 = Xie Zhiqing’s a history of modern Chinese fiction and the acceptance limit for Zhang Ailing in the literary history of China’s Mainland - 许维贤 Xu, Wei-xian (2015)
论文从张爱玲入史的个案来探讨夏志清的《中国现代小说史 》和中国大陆现代文学史的两种不同生成环境。前者倾向于研究型文学史 ,后者大部分是教科书文学史 ,这不同的书写取向是如何导致书写范式的两种不同选择:风格史和精神史的对立。论文先从新世纪夏志清和刘再复对张爱玲的有关争论 ,回顾了建国前后中国大陆对张爱玲的接受史 ,是后来如何围绕在夏志清的《中国现代小说史 》有关争论和影响中展开。最后对《中国现代小说史 》和中国新时期以来数十部现代文学史的张爱玲论述 ,做出了比较、分析和检讨 ,并指出了精神史的书写范式是如何紧附着意识形态的幽灵 ,始终跟随着新时期的张爱玲论述 ,它在大陆史家的心眼上划上了一道对张爱玲的接受限度 ,甚至从中我们可以归纳出几则大陆现代文学史书写在论述张爱玲的几条“金科玉律 ”,而这些至今都在无形中导致了大陆文学史写作以很暧昧的态度欲迎还拒着张爱玲幽魂的海外归来。Through a case study of Zhang Ailing’s position in the Chinese literary history, this paper attemp ts to exp lore two diverse generative environments for Xie Zhiqing’s A History of Modern Chinese Fiction and the history of modern Chinese literature. As Xie’s book is a research-oriented literary history while the history of modern Chinese literature is for the major part the literary history intended for textbooks, their respective orientation in compilation has resulted in two diverse choices in the paradigms of writing: the conflict between the style history and the spirit history. Starting with the disputes over Zhang Ailing between Xie Zhiqing and Liu Zaifu since the new century, this paper reviews how the history of Zhang Ailing’s acceptance in China’s mainland before and after the founding of the People’s Republic of China has been centered round the disputes over and impact of Xie Zhiqing’s A History of Modern Chinese Fiction. Finally this paper compares, analyzes and examines the descriptions of Zhang Ailing in A History of Modern Chinese Fiction and in dozens of modern Chinese literary history books since the new period. It is pointed out that the writing paradigm for the spirit history, colored by ideology, has affected the description of Zhang Ailing in modern Chinese literary history books, thus having retrained the fair portrayal of Zhang Ailing in modern Chinese literary history.